Association between serum 25-hydroxyvitamin D and diabetic kidney disease in Chinese patients with type 2 diabetes - Xie, Shaofeng; Huang, Liji; Cao, Wen; Hu, Yongxin; Sun, Hongping; Cao, Lin; Liu, Kemian; Liu, Chao (PloS one, 2019)
The objective was to assess the association between 25-hydroxyvitamin D (25OHD) level and diabetic kidney disease (DKD) in Chinese patients with type 2 diabetes. Data pertaining to 351 in-patients with type 2 diabetes were collected. Subjects were classified into three groups based on the level of urinary albumin-to-creatinine ratio (UACR). UACR < 30 mg/g was defined as normoalbuminuria, while UACR levels of 30-300 mg/g and ≥ 300 mg/g were defined as microalbuminuria and macroalbuminuria, respectively. Serum 25OHD and other clinical characteristics among various UACR groups were compared. The relationship between albuminuiria and 25OHD was analyzed. The prevalence of 25OHD insufficiency in the microalbuminuria group was significantly higher than that in the normoalbuminuria group (25.1% vs. 19.6%; P < 0.05); patients with macroalbuminuria had the highest prevalence of 25OHD deficiency (37.8%; P < 0.01 versus normoalbuminuria). Logistic regression analyses demonstrated that low 25OHD levels were associated with DKD [odds ratio (OR) = 1.51, 95% confidence interval (CI) 1.16-1.97). The association was more robust after adjusting for sex, hypertension, increased systolic blood pressure, glycemic status, and hyperuricemia (OR = 1.62, 95% CI 1.19-2.20). The prevalence of vitamin D insufficiency/deficiency in patients with albuminuria was overtly higher than that in patients without albuminuria among Chinese adults with type 2 diabetes. Vitamin D insufficiency/deficiency was independently associated with DKD in type 2 diabetes.